Papers on pragmasemantics - Benz, Anton; Blutner, Reinhard (ZAS Papers in Linguistics, 2009)
Optimality theory as used in linguistics (Prince & Smolensky, 1993/2004; Smolensky & Legendre, 2006) and cognitive psychology (Gigerenzer & Selten, 2001) is a theoretical framework that aims to integrate constraint based knowledge representation systems, generative grammar, cognitive skills, and aspects of neural network processing. In the last years considerable progress was made to overcome the artificial separation between the disciplines of linguistic on the one hand which are mainly concerned with the description of natural language competences and the psychological disciplines on the other hand which are interested in real language performance. The semantics and pragmatics of natural language is a research topic that is asking for an integration of philosophical, linguistic, psycholinguistic aspects, including its neural underpinning. Especially recent work on experimental pragmatics (e.g. Noveck & Sperber, 2005; Garrett & Harnish, 2007) has shown that real progress in the area of pragmatics isn’t possible without using data from all available domains including data from language acquisition and actual language generation and comprehension performance. It is a conceivable research programme to use the optimality theoretic framework in order to realize the integration. Game theoretic pragmatics is a relatively young development in pragmatics. The idea to view communication as a strategic interaction between speaker and hearer is not new. It is already present in Grice' (1975) classical paper on conversational implicatures. What game theory offers is a mathematical framework in which strategic interaction can be precisely described. It is a leading paradigm in economics as witnessed by a series of Nobel prizes in the field. It is also of growing importance to other disciplines of the social sciences. In linguistics, its main applications have been so far pragmatics and theoretical typology. For pragmatics, game theory promises a firm foundation, and a rigor which hopefully will allow studying pragmatic phenomena with the same precision as that achieved in formal semantics. The development of game theoretic pragmatics is closely connected to the development of bidirectional optimality theory (Blutner, 2000). It can be easily seen that the game theoretic notion of a Nash equilibrium and the optimality theoretic notion of a strongly optimal form-meaning pair are closely related to each other. The main impulse that bidirectional optimality theory gave to research on game theoretic pragmatics stemmed from serious empirical problems that resulted from interpreting the principle of weak optimality as a synchronic interpretation principle. In this volume, we have collected papers that are concerned with several aspects of game and optimality theoretic approaches to pragmatics.